New methodological approach to express assessment of ecological state for the coastal sea waters - S. V. Kholodkevich; T. V. Kuznetsova; A. S. Kurakin; A. A. Soldatov; O. L. Gostukhina; I. V. Golovina; Т. I. Andreenko; M. P. Kirin (Известия ТИНРО, 2018)
New methodological approach to express assessment of ecological state in the coastal areas of the Black Sea is proposed on the base of functional state evaluation for mussel Mytilus galloprovincialis. Non-invasive cardiac activity of mussels under a short-term functional loading (salinity change) was monitored in four differently polluted sites at Sevastopol city to detect early signs of their physiological state deterioration. As the control, the biochemical method of antioxidative stress (AOS) assessment was applied that is widely implicated in bioindication of marine environments. The sites in the Yuzhnaya/South Bay were defined as the most contaminated ones where the mussels demonstrated a prolonged recovery of the heart rate (76.8 min) and high variation of the heart rate after loading (24 %), while the mussels from the Kazachya Bay had rapid recovery (35.3 min) and lower variation of the heart rate (9 %) after removal of the stress load. The biochemical assessment showed the same results. The poor ecological state of the South Bay is obviously caused by heightened concentrations of heavy metals, as Pb, Sn, and Cu, detected in the hepatopancreas of tested mussels. The levels of antioxidative system parameters (e.g. glutathione peroxidase, catalase, and superoxide dismutase activity) correlated significantly with Pb content in the hepatopancreas (R2 = 0.89–0.92) and were heightened, as well. Prospects of the proposed biomarkers application in biomonitoring and their relevance for the risk assessment in aquatic ecosystems are discussed.